SANITARY-HYGIENIC PECULIARITIES OF GREENING OF STREETS AND AUTOMOBILE STATIONS AND NATIONAL POINTS - Ubaidullaev Farkhod Bakhtiyarullaevich; Ubaydullayev Abbosjon Azimjon O`G`Li; Qo’chqorov Yakubjon Ismagilovich (Galaxy International Interdisciplinary Research Journal, 2023)
Particular attention is paid to the improvement of the ecological and sanitary environment of our capital, the improvement and landscaping of local roads, as well as research on the development of effective and optimal methods for organizing parks and alleys where residents can enjoy cultural recreation as a priority.